Does Equity in Ways Of Showing Love Matter for Marital Satisfaction? - Kamenov, Željka (Array, 2011)
According to equity theory, the most satisfying relationships are ones where partners get out of the relationship as much as they put into it. The aim of this study was to examine whether the theory applies to the ways partners show love to each other. We tested 302 Croatian married couples of different age (20 - 82 years) and from various urban/rural backgrounds. Marriage length varied between one month and 57 years. Along with asking about marital satisfaction, we administered The Ways of Showing Love Scale. Equity was assessed as a similarity between how much (and specific ways in which) an individual shows love to his/her partner and his/her perception of how his/her partner shows love to him/her. Individuals who show and perceive a similar amount of love, no matter whether this amount is big or small, should be more satisfied with their relationship. Individuals who are underbenefited should be less satisfied, while individuals who are overbenefited should be somew here in the middle. According to equity theory, discrepancies in specific ways of showing love should not be relevant. Results didn't confirm these hypotheses. We found that both men and women with a high score on both showing and perceiving love are most satisfied with their marriage. Underbenefited and overbenefited individuals do not differ, and have somewhat lesser scores on marital satisfaction. Those with a low score on both showing and perceiving love are the least satisfied. We obtained the same pattern of results for all specific ways of showing love.